An empirical analysis of three local banks' performance over a ten-year period. - Leo, Hee Xun. (2013)
This paper seeks to investigate Singapore’s banking sector performance based on their abnormal returns during the global financial crisis, caused by the United States subprime mortgage crisis. Viewed as one of the most dramatic crisis to date, the 2008 crisis created an economic pandemic that affected the global economy, particularly financial institutions such as banks. The Singapore banking sector appeared relatively resilient to the crisis as it recovered fairly quickly compared to foreign counterparts.